PREDICTIVE MODELLING FOR STRESS MANAGEMENT OF HEALTHCARE EMPLOYEES - Katyayani, J; Varalakshmi, Ch. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The healthcare sector and healthcare professionals were essential during the COVID-19 epidemic. There is an enormous need for workers in the healthcare sector due to the necessity of industry. Professionals in this field must endure a great deal of pressure at work due to irregular hours and demanding schedules. The goal of this study is to evaluate the stress levels and stress management strategies of healthcare workers. This study focuses on a number of factors, including the age, gender, and marital status of the employees as well as physical working conditions, timely deadlines, co-worker cooperation, individual health issues, working conditions, improved compensation and training for job performance, and cooperation within the family. How they are employing methods that reduce stress to manage their stress.